Problematics of Implementing The MBKM (Independent Learning Campus Independent) Curriculum In The History Education Study Program FKIP Unmas Denpasar - Anto, Ruli; Ari, Ida Ayu Nyoman Maye Denia; Lasmawan, I Wayan; Suharta, I Gusti Putu; Sartika, Lianda Dewi (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
The aim of this research is to find problems in implementing the MBKM curriculum, which is a new curriculum, implemented by the Ministry of Education, Culture, Research and Technology to provide students with independence in organizing their study time. However, there are several challenges in its implementation in the History Education Study Program, FKIP, Mahasaraswati University, Denpasar. This type of research is qualitative with a phenomonological approach. The data collection technique in this research went through the stages of observation, source interviews, and documentation collection. Testing the validity of the data by reducing the data, explaining the data, and drawing conclusions. This research produces data related to the problems experienced in implementing MBKM, namely 1) Limited human resources (lecturers and support staff) to guide and accompany students optimally in organizing study time. The ratio of lecturers and students is not appropriate. 2) Limited supporting infrastructure for the Independent Learning program such as laboratories, libraries and other supporting facilities. 3) Student independence is still low in organizing study time effectively and efficiently according to the expected competencies. 4) Lack of flexible curriculum readiness to accommodate various individual student learning needs. 5) The assessment and evaluation system is not yet optimal for measuring the achievement of the expected competencies from the Merdeka Belajar program. Therefore, systemic improvement efforts are needed to optimize the implementation of the MBKM Curriculum in the History Education Study Program, FKIP, Mahasaraswati University, Denpasar.